Optimalisasi Teknologi Digital Dalam Tantangan Lingkungan Era Disruptif (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
In the current disruptive era, environmental challenges are increasingly complex with pressure on natural resources and sustainability. In this context, optimizing digital technology is crucial for providing innovative solutions. This research aims to explore the role of digital-based technology, such as Internet of Things (IoT), intelligence (AI) and blockchain systems in overcoming environmental challenges. In-depth analysis was carried out to identify how the application of these technologies has influenced conventional paradigms, provided efficiencies, and strengthened risk mitigation efforts against negative environmental impacts. Wise integration and optimization of digital technology not only provides solutions to today's environmental challenges, but also provides opportunities for future revolution. By maximally utilizing the potential of digital technology, it is hoped that a system that is more adaptive and responsive to environmental changes can be created. Through this article, it is hoped that it can provide deeper insight into how digital technology can be a catalyst in efforts to maintain environmental sustainability amidst the turmoil of the disruptive era.